Dynamics of physico-chemical properties and safety indicators of fermented wheat bran - Karmazin A.P.; Mironova O.A.; Mironova A.A. (E3S Web of Conferences, 2024)
The article is devoted to the study of quality and safety indicators of wheat bran under the influence of microbiological fermentation. Wheat bran is the main by-product of deep processing of wheat, formed at the stage of grain purification and crushing, and accounts for about 15% of its weight. The purpose of our research was to study the effect of microbiological fermentation of wheat bran on the quality and safety of the resulting product during fermentation for 12 and 24 hours. It was found that after 12- and 24-hour fermentation of wheat bran with Lesnov's starter culture, the mass fraction of protein, soluble carbohydrates, starch increased; the mass fraction of moisture, fat, and crude fiber content decreased in comparison with the initial level; pH shifted to the alkaline side. CFU/g of mold fungi and yeast cells, the content of mycotoxins, pesticides, nitrates and nitrites, heavy metals, GMOs in wheat bran were in quantities below the minimum MAC level both before and after fermentation, regardless of the fermentation time.